Stochastic Discounted Cash Flow A Theory of the Valuation of Firms - Kruschwitz, Lutz (Springer Texts in Business and Economics, 2020)
This open access book discusses firm valuation, which is of interest to economists, particularly those working in finance. Firm valuation comes down to the calculation of the discounted cash flow, often only referred to by its abbreviation, DCF. There are, however, different coexistent versions, which seem to compete against each other, such as entity approaches and equity approaches. Acronyms are often used, such as APV (adjusted present value) or WACC (weighted average cost of capital), two concepts classified as entity approaches. This book explains why there are several procedures and whether they lead to the same result. It also examines the economic differences between the methods and indicates the various purposes they serve. Further it describes the limits of the procedures and the situations they are best applied to. The problems this book addresses are relevant to theoreticians and practitioners alike.